Rising protectionism and global value chains: Quantifying the general equilibrium effects - Rita Cappariello; Vanessa Gunnella; Sebastian Franco-Bedoya; Gianmarco Ottaviano (European Central Bank (ECB), 2020)
Quantifying the effects of trade policy in the age of "global value chains" (GVCs) requires an enhanced analytical framework that takes the observed international input-output relations in due account. However, existing quantitative general equilibrium models generally assume that industry-level bilateral final and intermediate trade shares are identical, and that the allocation of imported inputs across sectors is the same as the allocation of domestic inputs. This amounts to applying two proportionality assumptions, one at the border to split final goods and inputs, and another behind the border to allocate inputs across industries. In practice, neither assumption holds in available input-output data sets. To overcome this limitation of existing models, we consider a richer input-output structure across countries and sectors that we can match with the actual structure reported in input-output tables. This allows us to investigate the relation between the effects of changes in trade policies and GVCs. When we apply the enhanced quantitative general equilibrium model to the assessment of the effects of Brexit, we find trade and welfare losses that are substantially larger than those obtained by previous models. This is due to the close integration of UK-EU production networks and implies that denser GVCs amplify the adverse effects of protectionist trade policies.
Keywords: F13; F15; F40; F60; 330; Trade model; supply chains; Trade policy shocks; Brexit